Retrospective analysis: The application of human menopausal gonadotropin combined with letrozole for IUI in patients undergoing artificial insemination by husband due to unexplained or mild male factors - Li, Hua-qing; Pan, Xin-ling; Su, Nian-jun; Lu, Xi-ping; Chen, Jun-qing; Chen, Xu-wei (Frontiers in Endocrinology, 2022)
Objective To compare the effects of human menopausal gonadotropin (HMG) combined with letrozole (LE) to HMG only for ovarian stimulation on pregnancy outcome of infertile patients undergoing artificial insemination by husband (AIH) due to unexplained or mild male factors. Materials and methods Infertile patients with unexplained or mild male factors treated from July 2015 to December 2021 were selected as subjects. The patients were divided into two groups according to the ovarian stimulation schemes they received, namely HMG combined with LE or HMG only. We analyzed the laboratory examination results before drug treatment (baseline) and during ovarian stimulation and compared the pregnancy outcomes of the two groups using univariable analysis and multivariable logistic regression analysis. Results In total, 526 cycles of 372 couples were included. The univariate analysis showed that the clinical pregnancy rate of the HMG combined with LE group was 24.8%, significantly higher than that of the HMG group (14.8%, P = 0.007). The live birth rate (19.9%) of the HMG combined with LE group were also significantly higher than those of the HMG group (11.2%, respectively). In multivariate logistic analysis, the age of males was negatively associated with the clinical pregnancy rate (OR 0.874, 95% CI 0.793 0.963, P=0.006) and live birth (OR0.875, 95% CI 0.783 0.977, P=0.018). Moreover, ovarian stimulation with HMG+LE was the only beneficial factor significantly associated with clinical pregnancy (OR 1.929, 95% CI 1.068 3.485, P=0.029) and live birth (OR 2.255, 95% CI 1.188 4.282, P=0.013). Conclusion Ovarian stimulation using HMG combined with LE can increase the clinical outcomes (live birth and clinical pregnancy) among infertile patients undergoing AIH due to explained or mild male factors.